2015
DOI: 10.1007/s00586-015-4215-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of thoracic scoliosis in adults 25 to 64 years of age detected during routine chest radiographs

Abstract: We found a 13.4 % prevalence of thoracic scoliosis among asymptomatic adults aged 25-64 years on routine outpatient chest radiographs. 11.6 % of patients demonstrated a coronal curvature between 10° and 19°. Unlike prior studies evaluating asymptomatic thoracic curves in elderly patients, age and gender did not significantly affect curve magnitude in our younger cohort. These data may provide a reference point to help clinicians counsel asymptomatic patients diagnosed with thoracic scoliosis on routine chest r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
0
5
0
5
Order By: Relevance
“…However, in other epidemiological studies, the prevalence of thoracic scoliosis on chest radiographs of asymptomatic adults is 8-24% [15][16][17]. On the one hand, the prevalence provided by our study may underestimate the prevalence of scoliosis in PCD, because a minority of our population was still prepubertal, 31% of our population was under the age of ten.…”
Section: Discussionmentioning
confidence: 53%
“…However, in other epidemiological studies, the prevalence of thoracic scoliosis on chest radiographs of asymptomatic adults is 8-24% [15][16][17]. On the one hand, the prevalence provided by our study may underestimate the prevalence of scoliosis in PCD, because a minority of our population was still prepubertal, 31% of our population was under the age of ten.…”
Section: Discussionmentioning
confidence: 53%
“…Despite the frequent citation of the overall prevalence of 1.5-3% for idiopathic scoliosis, Konieczny et al have demonstrated that the prevalence of idiopathic scoliosis as reported in epidemiological studies varies widely and is dependent of age, gender, race and screening methodology: They found prevalences reported between 0.47 and 11.1% [3]. Even, in epidemiological studies that are most comparable to our design (screening on chest X-rays), the prevalence of thoracic scoliosis is 8-24% [4][5][6]. Therefore, we would like to remind the readers that the prevalence of scoliosis in our population of PCD patients (8%) is within the range reported for the prevalence of scoliosis in the general population.…”
mentioning
confidence: 56%
“…Küçük açılı skolyozlar OSTP sırasında gözden kaçabilirken (1,10) direkt grafilerle kolayca saptanabilirler (3). Bu çalışmada akciğer grafisi çektirmiş adölesanlarda torasik skolyoz prevalansının belirlenmesi amaçlandı.…”
Section: Discussionunclassified
“…Adölesan dönemde en sık karşılaşılan omurga sorunu olan skolyoz, omurga diziliminin koronal düzlemde 10 o veya daha büyük bir açıda bozuk olmasıdır (1)(2)(3). Küçük açılı skolyoz hastalarında (10-20 o ) herhangi bir belirti görülmeyebilir.…”
Section: Introductionunclassified
See 1 more Smart Citation